Cardiovascular Risk Factors in Subclinical Hypothyroidism: A Case Control Study in Nepalese Population. (7th October 2015) - KC, Rajendra; Khatiwada, Saroj; Deo Mehta, Kishun; Pandey, Pratikshya; Lamsal, Madhab; Majhi, Shankhar
Abstract : Objectives . To assess cardiovascular risk factors in Nepalese population with subclinical hypothyroidism as compared to age and sex matched controls. Materials and Methods . A case control study was conducted among 200 subjects (100 subclinical hypothyroid and 100 euthyroid) at B.P. Koirala Institute of Health Sciences, Dharan, Nepal. Demographic and anthropometric variables including systolic and diastolic blood pressure (BP) were taken. Blood samples were assayed for serum free triiodothyronine (fT3), free thyroxine (fT4), thyroid stimulating hormone (TSH), total cholesterol (TC), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), and high sensitivity C reactive protein (hs-CRP). Results . Subclinical hypothyroid patients had significantly higher diastolic BP, total cholesterol, LDL cholesterol, and hs-CRP than controls. The odds ratio of having hypercholesterolemia (>200 mg/dL), low HDL cholesterol (<40 mg/dL), undesirable LDL-cholesterol (>100 mg/dL), high hs-CRP (>1 mg/L), and high diastolic BP (>80 mmHg) and being overweight (BMI ≥ 23 Kg/m 2 ) in subclinical hypothyroidism was 2.29 (95% CI; 1.2–4.38, p = 0.011 ), 1.73 (95% CI; 0.82–3.62, p = 0.141 ), 3.04 (95% CI; 1.66–5.56, p < 0.001 ), 2.02 (95% CI; 1.12–3.64, p = 0.018 ), 3.35 (95% CI; 1.72–6.55, p < 0.001 ), and 0.9 (95% CI; 0.48–1.67, p = 0.753 ), respectively, as compared to controls. Conclusion . Subclinical hypothyroid patients are associated with higher risk for cardiovascular disease than euthyroid subjects.